Disaggregate Level Evidence on Monetary Neutrality - Gauger, Jean (The Review of Economics and Statistics, 1988)
Existing tests of the neutrality hypothesis focus on aggregate level economic activity. However, failure to examine disaggregate level effects can lead to incorrect inferences concerning anticipated and unanticipated money growth impacts. Disaggregate level testing of neutrality is limited. Also receiving inadequate attention is the impact upon test inferences of the use of in the widely used two-step estimation procedure. This research tests neutrality across eleven manufacturing industries and aggregate GNP, incorporating a correction for generated regressors into GLS estimation. The research finds non-neutrality of anticipated money at the disaggregate level under two general money forecasting specifications.